Quantitative Assessment of Apical Debris Extrusion and Intracanal Debris in the Apical Third, Using Hand Instrumentation and Three Rotary Instrumentation Systems - H.K., Sowmya (JCDR Research and Publications (P) Limited, 2014)
Introduction: Decreased apical extrusion of debris and apical one third debris have strong implications for decreased incidence of postoperative inflammation and pain. Thus, the aim of this study was to assess quantitatively the apical extrusion of debris and intracanal debris in the apical third during root canal instrumentation using hand and three different types of rotary instruments. Methodology: Sixty freshly extracted single rooted human teeth were randomly divided into four groups. Canal preparation was done using step-back with hand instrumentation, crown-down technique with respect to ProTaper and K3, and hybrid technique with LightSpeed LSX. Irrigation was done with NaOCl, EDTA, and normal saline and for final irrigation, EndoVac system was used. The apically extruded debris was collected on the pre-weighed Millipore plastic filter disk and weighed using microbalance. The teeth were submitted to the histological processing. Sections from the apical third were analyzed by a trinocular research microscope that was coupled to a computer where the images were captured and analyzed using image proplus V4.1.0.0 software. The mean weight of extruded debris for each group and intracanal debris in the root canal was statistically analyzed by a Kruskal-Wallis one-way analysis of variance and Mann-Whitney U test. Results: The result showed that, hand instrumentation using K files showed the highest amount of debris extrusion apically when compared to ProTaper, K3 and LightSpeed LSX. The result also showed that there was no statistically significant difference between the groups in relation to presence of intracanal debris in the apical one third. Conclusion: Based on the results, all instrumentation techniques produced debris extrusion. The engine driven Ni-Ti systems extruded significantly less apical debris than hand instrumentation. There was no statistically significant difference between the groups in relation to presence of intracanal debris in the apical one third.